Enhancing Visible‐Light Hydrogen Evolution Performance of Crystalline Carbon Nitride by Defect Engineering. Issue 14 (17th May 2019) - Ren, Wei; Cheng, Jiajia; Ou, Honghui; Huang, Caijin; Titirici, Maria‐Magdalena; Wang, Xinchen
Abstract: Crystalline carbon nitride (CCN)‐based semiconductors have recently attracted widespread attention in solar energy conversion. However, further modifying the photocatalytic ability of CCN always results in a trade‐off between high crystallinity and good photocatalytic performance. Herein, a facile defect engineering strategy was demonstrated to modify the CCN photocatalysts. Results confirmed that the obtainedD ‐CCN maintained the high crystallinity; additionally, the hydrogen production rate ofD ‐CCN was approximately 8 times higher than that of CCN. Particularly, it could produce H2 even if the incident light wavelength extended to 610 nm. The significantly improved photocatalytic activity could be ascribed to the introduction of defects into the CCN polymer network to form the midgap states, which significantly broadened the visible‐light absorption range and accelerated the charge separation for photoredox catalysis. Abstract : Effective defects : A facile defect engineering strategy is developed to create defects into crystalline carbon nitride (CCN). The obtained D‐CCN exhibits an enhanced photocatalytic performance owing not only to the maintaining of high crystallinity, but also to the presence of midgap states induced by introducing defects.